Sufizm w Dagestanie - Siereda, Natalia (Studia Azjatystyczne, 2019)
The article describes the religious situation in Daghestan, one of the north-Caucasian republics of Russia, focusing especially on the Islamic mysticism – Sufism. The introduction presents the geographical and ethnical situation of the Republic. The following chapters discuss the history of Islam in Caucasus which had started in Daghestan as well as the development of mystical brotherhoods and their profiles. The role of Islam and its mystical branch in contemporary Daghestan has been depicted in the conclusion.